MIND-VR: Design and Evaluation Protocol of a Virtual Reality Psychoeducational Experience on Stress and Anxiety for the Psychological Support of Healthcare Workers Involved in the COVID-19 Pandemic - Pallavicini, Federica; Orena, Eleonora; di Santo, Simona; Greci, Luca; Caragnano, Chiara; Ranieri, Paolo; Vuolato, Costanza; Pepe, Alessandro; Veronese, Guido; Dakanalis, Antonios; Rossini, Angelo; Caltagirone, Carlo; et al. (Frontiers in Virtual Reality, 2021)
To ensure the continuity of healthcare and to counter the spread of the COVID-19 pandemic, doctors and nursing staff at hospitals must face an insidious, invisible danger that is stretching the healthcare system far past its capacity. Excessive workload, inadequate protection from contamination, the need to manage patients experiencing extreme suffering and being kept apart from their families put medical personnel at high risk to experience stress and anxiety. Numerous scientific studies have shown that, among various therapeutic programs, virtual reality represents a highly specialized and effective tool for the prevention and treatment of stress and anxiety. However, the solutions developed using this technology for the management of stress and anxiety induced by the COVID-19 pandemic are still very limited, and none of these have been developed specifically for use with healthcare professionals. Therefore, this paper will detail the design and evaluation protocol of MIND-VR, a virtual reality-based psychoeducational experience on stress and anxiety developed following a user-centered design approach. The virtual experience will be tested on a sample of Italian hospital healthcare personnel involved in the COVID-19 pandemic emergency. MIND-VR is available free of charge, both in Italian and English, on the project website (https://mind-vr.com/).